ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEMANFAATAN DAN PENGGUNAAN SISTEM INFORMASI - Sultan, Adib (Universitas Pendidikan Indonesia, 2014)
This research aimed to examine some factors that influence to intention of utilization of information system and information system usage at PT. X. The reason for study is because of the differences in some results of previous study, so examination need to be done again. The method was used in the data collection is survey method, in this case data were obtained by distributing questionnaires to the respondents. The obtained research data is based on accounting information system users respondent’s perception by 31 respondents. Methods of research data using validity test, reliability test, and classical assumptions test, then hypothesis test using multiple linear regression model. The data were analyzed using multiple regression by SPSS 19 software. Result of this study show that performance expectancy, effort expectancy and social factor are significant influence to intention of information system. Facilitating conditions and intention of accounting information system was significant influence to information system usage.